Di(2-ethylhexyl) phthalate mediates IL-33 production via aryl hydrocarbon receptor and is associated with childhood allergy development - Tsai, Mei-Lan; Hsu, Shih-Hsien; Wang, Li-Ting; Liao, Wei-Ting; Lin, Yi-Ching; Kuo, Chang-Hung; Hsu, Ya-Ling; Feng, Ming-Chu; Kuo, Fu-Chen; Hung, Chih-Hsing (Frontiers in Immunology, 2023)
Background: Few studies assess cord blood biomarkers to predict prenatal exposure to di(2ethylhexyl) phthalate (DEHP) on the development of allergic diseases later in childhood. IL-33 has been indicated to play an important role in allergic diseases. We evaluated the association of prenatal DEHP exposure and IL-33 in cord blood on the development of allergic diseases. We also investigated the mechanism of DEHP in human lung epithelial cells and asthma animal models.Methods: 66 pregnant women were recruited, and their children followed when they were aged 3 years. Maternal urinary DEHP metabolites were determined using liquid chromatographyelectrospray-ionization-tandem mass spectrometry. The effect of DEHP on IL-33 production was investigated in human lung epithelial cells and club cell-specific aryl hydrocarbon receptor (AhR) deficiency mice. ELISA and RT-PCR, respectively, measured the IL-33 cytokine concentration and mRNA expression.The concentrations of maternal urinary DEHP metabolites and serum IL-33 in cord blood with childhood allergy were significantly higher than those in the non-childhood allergy group. DEHP and MEHP could induce IL-33 production and reverse by AhR antagonist and flavonoids in vitro. Enhanced ovalbumin-induced IL-4 and IL-33 production in bronchoalveolar lavage fluid (BALF) by DEHP exposure and suppressed in club cell-specific AhR null mice. Kaempferol has significantly reversed the DEHP effect in the asthma animal model.Cord blood IL-33 level was correlated to childhood allergy and associated with maternal DEHP exposure. IL-33 might be a potential target to assess the development of DEHPrelated childhood allergic disease. Flavonoids might be the natural antidotes for DEHP.